Effects of Different Rehabilitation Methods and Soil Parameters on the Establishment of Forest Tree Seedlings in a Degraded Forest - Bahar Dj., Maswar (2000)
The degradation of forests not only results in the loss of productive timber but also many other socio-economic and ecological problems. Thus, rapid forest recovery of the logged-over forest is important. Amongst the strategies that can be used to establish productive forest are selection of plant species, methods of establishment and subsequent vegetation management techniques. Therefore, the objectives of this study are: 1) to identify suitable methods for rehabilitation of logged-over forest and 2) to identify the most important soil parameters affecting seedling growth. The study was carried out on a degraded logged-over lowland tropical forest, located in Pasoh Forest Reserve, Negeri Sembilan, Peninsular Malaysia. Four rehabilitation methods tested were: Tl for line planting, with lines set from west to east with a width of 3m, 5m and 10m and distance between lines was 10m; T2 for gap planting of 1 0m x 1 0m x 5/ha; T3 for gap planting of 20m x 20m x 5/ha; and T4 for gap planting of 1 0m x 1 0m x 9/ha. The lines and gaps were planted with three timber species namely Azadirachta excelsa, Hopea odorata, and Vitex pubescens. The suitability of the methods was evaluated by measuring seedlings survival, biomass production, changes in soil properties and cost establishment. One year after planting, height increment of seedlings of Azadirachta excelsa and Hopea odorata was measured. Vitex pubescens was not included because there was no visible growth increment during the one-year period. Soil samples from the surface soil were collected from the vicinity of the seedlings for the determination of physical and chemical properties. Statistical analysis was conducted in order to establish relationships between soil parameters and seedlings growth. The results showed that there were no significant difference in the survival of the seedlings of all species one-year after planting and they adapted quite well to degraded soil conditions. This implies that all the rehabilitation methods and species are suitable for rehabilitation of degraded logged-over forest in this area. However, in term of biomass production Tl was found to be the best method of rehabilitation but in term of cost T2 was found to be the cheapest. The simple regression equations between soil parameters and height increment showed that the soil parameters limiting the growth of Azadirachta excelsa are thickness of A-horizon, texture, penetration resistance, available water capacity, organic matter, and exchangeable Ca and Mg. For Hopea odorata, the limiting growth factors are thickness of A-horizon, macro-pore space and penetration resistance. However, the multiple linear regressions showed that the growth of young seedlings Azadirachta excelsa, and Hopea odorata is affected not only by single soil parameters but also by an interaction of several soil parameters.